Incidence of digital papillomatosis ("hairy warts") in a dairy herd. Response to surgery and autogenous vaccination - J. Gaines; J. Galland; J. Leedle; R. Basaraba (Kansas Agricultural Experiment Station Research Reports, 1993)
Digital papillomatosis (hairy warts) was diagnosed in a dairy herd with a high level of lameness (20%). Warts ranged from mild to moderate to severe, with severity increasing with length of lactations. All milking cows (100%) had at least mild lesions. Cows with severe lesions were more likely to be lame. Severity of lesions had no influence on 305-day ME milk production, days open, or somatic cell counts. Cows in milk more than 150 days and lame produced 3 kg less milk per day than cows that were not lame. Almost all warts were in the interdigital cleft near the heel of the rear feet. A few cows had lesions in the front of the interdigital cleft or on the front feet. No viral particles were observed or isolated. A new, Gram-negative, motile, facultatively anaerobic, spiral-shaped bacteria was isolated from one lesion. The cellular fatty acid profile of this bacterium had no match to any other known bacteria in any of three computer databases examined. Cows with severe lesions were assigned randomly to one of four groups: Group 1: surgical removal and autogenous vaccination; Group 2: surgical removal only; Group 3: autogenous vaccination only, and Group 4: control. Neither surgical removal nor autogenous vaccination had a significant effect on wart severity, lameness, or milk production when cows were inspected 10 wk later. Contemporary evaluation of 249 herdmates revealed a substantial number of severely affected cows naturally improved. Of 25 severely affected herd contemporaries, only 8 were severely affected 10 wk later. Evidently, natural improvement of lesions is a common phenomenon with "hairy warts. "; Dairy Day, 1993, Kansas State University, Manhattan, KS, 1993;
Keywords: Dairy Day; 1993; Kansas Agricultural Experiment Station contribution; no. 94-149-S; Report of progress (Kansas Agricultural Experiment Station); 694; Dairy; Bovine; Lameness; Digital papillomatosis